2018
DOI: 10.1002/nbm.3934
|View full text |Cite
|
Sign up to set email alerts
|

Towards the complex dependence of MTRasym on T1w in amide proton transfer (APT) imaging

Abstract: Amide proton transfer (APT) imaging is a variation of chemical exchange saturation transfer MRI that has shown promise in diagnosing tumors, ischemic stroke, multiple sclerosis, traumatic brain injury, etc. Specific quantification of the APT effect is crucial for the interpretation of APT contrast in pathologies. Conventionally, magnetization transfer ratio with asymmetric analysis (MTR ) has been used to quantify the APT effect. However, some studies indicate that MTR is contaminated by water longitudinal rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…For the next step, this acquisition protocol will be used to comprehensively assess the actual clinical relevance of relaxation compensation in CEST‐MRI for various neuro‐oncological clinical questions. In particular, the translation to 3 T enables investigation of the controversially discussed overcompensation of T 1 at this magnetic field strength using the AREX approach (Equation ) . The unravelling of the different CEST signals and compensation for competing relaxation effects by the presented acquisition protocol can also enable obtaining more detailed information on the origin of CEST contrast in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For the next step, this acquisition protocol will be used to comprehensively assess the actual clinical relevance of relaxation compensation in CEST‐MRI for various neuro‐oncological clinical questions. In particular, the translation to 3 T enables investigation of the controversially discussed overcompensation of T 1 at this magnetic field strength using the AREX approach (Equation ) . The unravelling of the different CEST signals and compensation for competing relaxation effects by the presented acquisition protocol can also enable obtaining more detailed information on the origin of CEST contrast in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized a saturation power of 1.5 μT, which has proved to be capable of maintaining the dominant contribution of the APT effect in MTR asym analysis and generating good contrast between tumor and normal‐appearing brain tissues . In addition, a recent simulation study has demonstrated the insensitive MTR asym to T 1w at the saturation powers of 1–3 μT at 3T, due to a comparable T 1 recovery effect and T 1w ‐related saturation effect . Therefore, T 1w normalized APTw was not necessary under the current imaging settings.…”
Section: Discussionmentioning
confidence: 99%
“…CEST contrast computation using the proposed Z‐spectra fitting using both models 1 and 2 mitigates the MT effect and is less sensitive to T 1 ; however, complete removal of these effects from true CEST contrast has not been achieved to date. Another study reported that for nonsteady‐state acquisition, the effect of T 1 is substantially less. In this study, we have considered only two CEST pools and a single rNOE.…”
Section: Discussionmentioning
confidence: 99%
“…For simulation, the concentrations were taken from references , and exchange rate measured in vivo from rat brain . Three amine protons were considered for each glutamate molecule.…”
Section: Methodsmentioning
confidence: 99%